Cocreating with Young Fathers: Producing Community-Informed Training Videos to Foster more Inclusive Support Environments. (September 2022) - Way, Laura; Tarrant, Anna; Ladlow, Linzi; York, Jonah; Gorzelanczyk, Adam; Brown, Dylan; Patterson, Will
Our contribution draws upon a collaborative project called 'Diverse Dads', which ran between October 2020 and April 2021, during the 2020–2021 COVID-19 pandemic. The team comprised members of the North East Young Dads and Lads (NEYDL) Project, advisors from support organisations that champion inclusivity, and the Following Young Fathers Further (FYFF) research team. 'Diverse Dads' sought to identify and address gaps in service provision for young minoritised dads in the North East, and to promote cross-sector conversations concerning inclusive support for young dads from diverse communities. With support provided remotely by the FYFF team, peer research was undertaken by three young men from NEYDL. Our work highlights how methods of coproduction and cocreation were achieved during the pandemic. NEYDL is also embarking on an ambitious new digital service journey with partners DigiDAD, producing digital outputs that are made by and for young fathers. Working collaboratively, the peer research team and DigiDAD produced a set of videos designed to support training for professionals in mainstream, family, and statutory services. Showcasing one of these creative outputs, our contribution will discuss the continued value of coproduction and cocreation with young people and using creative, digital methods to support productive discussions between young fathers, professionals, and researchers.